Optimal redundancy allocation in series-parallel system using genralized fuzzy number - Mahapatra,G.S (Tamsui Oxford Journal of Mathematical Sciences)
In this paper generalized linear fuzzy numbers are used in redundancy allocation for optimum reliability of series-parallel system. Here reliability and cost of components of the system, system cost, and system weight are fuzzy numbers. We use geometric programming to solve redundancy allocation problem. The redundancy allocation problem whose aim is to find out the optimal allocation of redundancy components in such a way that maximizes the system reliability subjected to available total system cost and weight. Here it demonstrates to find a set of optimal solutions that help the decision maker to take the right decisions from the optimal solution set. Examples are displayed to illustrate the model utilizing generalized fuzzy numbers.